MANAJEMEN PROYEK COLD STORAGE MANGGIS DI LINGSAR: PROJECT MANAGEMENT ON MANGOSTEEN COLD STORAGE IN LINGSAR - Sujud Alfanza Jihad; Is Bunyamin Suryo; Anak Agung Alit Triadi (Energy, Materials and Product Design, 2025)
Mangosteen is the largest export commodity in the Lingsar sub-district, West Lombok district, West Nusa Tenggara. In addition to being sold in the local market, mangosteen in the Lingsar area is also exported to foreign countries such as China, the United Arab Emirates, and countries in Europe. One of the mangosteen exporters in the West Lombok area is PT BAS which has a warehouse as well as an operational location to store and manage mangosteen to be exported. To maintain the temperature of mangosteen, PT BAS uses Cold Storage to store harvested mangosteen for storage before being packaged and exported. The distribution is useful to maintain the content in mangosteen fruit so that it does not rot because it is stored in a closed room. So that mangosteen is ready for export This aims to maintain the quality of the stored mangosteen so that it is ready for export. Therefore, for cost and time efficiency, it is important to apply the design and simulation method to Cold Storage to find out the incoming levels and the company owner can monitor in real time the condition of the mangosteen stored in it.